2008
DOI: 10.1021/nl073163v
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Electrospun TiO2 Nanofibers with Pt Nanoparticles and Nanowires for Catalytic Applications

Abstract: This paper reports a simple procedure for derivatizing the surface of anatase TiO2 nanofibers with Pt nanoparticles and then Pt nanowires. The nanofibers were prepared in the form of a nonwoven mat by electrospinning with a solution containing both poly(vinyl pyrrolidone) and titanium tetraisopropoxide, followed by calcination in air at 510 degrees C. The fiber mat was then immersed in a polyol reduction bath to coat the surface of anatase fibers with Pt nanoparticles of 2-5 nm in size with controllable densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
351
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(352 citation statements)
references
References 25 publications
0
351
1
Order By: Relevance
“…The TiO 2 supported catalyst showed similar performance compared to carbon supported Pt in a H 2 PEM fuel cell when operated at 60 • C and 0.8 V. However, in the Ohmic regime the application of the ceramic support yielded lower performance due to its higher electrical resistance. Forno et al employed a reflux method to grow either Pt nanoparticles or nanowires on titania nanofibers [9]. The Pt nanowires had an approximate diameter of 7 nm and lengths of up to 125 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The TiO 2 supported catalyst showed similar performance compared to carbon supported Pt in a H 2 PEM fuel cell when operated at 60 • C and 0.8 V. However, in the Ohmic regime the application of the ceramic support yielded lower performance due to its higher electrical resistance. Forno et al employed a reflux method to grow either Pt nanoparticles or nanowires on titania nanofibers [9]. The Pt nanowires had an approximate diameter of 7 nm and lengths of up to 125 nm.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to explore alternative materials that can provide improved stability compared to carbon. Several research groups investigated titanium, tungsten and zirconium oxide supports with size features in the nanometer range [12][13][14][15][16][17][18]. Recent results in our group showed that Pt supported on titanium dioxide nanofibers is more stable compared to conventional carbon black [18].…”
Section: Introductionmentioning
confidence: 90%
“…Then, the build-up of electrostatic charges on the surface of a liquid droplet induces the formation of a jet, which is subsequently stretched to form continuous ultrathin¯bers. Li et al 74,75 and Formo et al 76 described a general procedure based on electrospinning for 1D porous TiO 2 NFs as well as their composite architectures with controllable diameters and porosities.…”
Section: Electrospinning Methodsmentioning
confidence: 99%